Influence of match status in ball possessions in the FIFA Women`s World Cup France 2019 - Iván-Baragaño, I.; Maneiro, R.; Losada, J. L.; Ardá, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
There is little scientific knowledge about the influence of the match status criteria (winning, drawing, losing) in ball possessions in women`s football. Therefore, the aims of this study were: (i) to discover how technical-tactical criteria in ball possessions in women`s football are modified based on the match status, and (ii) to find out which criteria provide the best probability for offensive success (i.e. goal, shot, and sent to area) under the influence of match status. To this end, 2323 ball possessions were analyzed in the FIFA Women`s World Cup France 2019 using observational methodology. Two types of analysis were applied: firstly, a bi-variate analysis between match status and the rest of the criteria, followed by a predictive multivariate binary logistic regression analysis. The results obtained from the bi-variate analysis reveal the existence of significant statistical differences in the start and development of ball possessions in this championship depending on the match status. On the other hand, there was no evidence of differences when it comes to goal scoring, shots, and passes into the area based on these criteria. From the logistic regression models used, it was observed that there is a common pattern of success regardless of the match status, consisting of ball possessions that start in forward zones, in contexts of offensive interaction and with the intention of rapid progression toward the opponent`s goal. These results could be used for planning match and training strategies in elite women`s football.